Voltaire Against the Jews, or The Limits of Toleration - Piazza, Marco. author. aut Link
IX, 182 p.
Keywords: This book challenges Voltaire’s doctrine of toleration. Can a Jew be a philosopher? And if so, at what cost? It seeks to provide an organic interpretation of Voltaire’s attitude towards Jews, problematising the issue against the background of his theory of toleration. To date, no monograph entirely dedicated to this theme has been written. This book attempts to provide an answer to the crucial questions that have emerged in the past fifty years through a process of reading and analysis that starts with the publication of Des Juifs (1756), and ends with the posthumous publication of the apocryphal article ‘Juifs’ in the Kehl edition of the Dictionnaire Philosophique (1784). Marco Piazza is Associate Professor at the University of Roma Tre, Italy.